Heal your brain : how the new neuropsychiatry can help you go from better to well - Hellerstein, David (Baltimore : Johns Hopkins University Press, 2011)
'Dr. Hellerstein, a psychiatrist at Columbia University's College of Physicians and Surgeons, puts this new form of psychiatry to the test. Depression and anxiety disorders damage the brain, but as Dr. Hellerstein explains, the right treatment can change the patterns of brain activity, brain cell connections, and even the brain's anatomy. To illustrate, he relates the stories of people as they travel through various phases of New Neuropsychiatry treatment, from evaluation to therapy to remission, and illustrates how this approach can help you progress through each phase as well'--Bk. jacket.
Includes bibliographical references and index.
Keywords: Neuropsychiatry; Brain; Stress (Psychology).